Investigating disease tolerance to Zymoseptoria tritici in wheat - Kock Appelgren, Petra S. (2017)
Disease tolerance is defined as the ability to maintain grain yield in the presence of disease and could be a potential defence mechanism to be incorporated into breeding programmes. It is an attractive goal, as disease tolerance has the potential to be a broad-spectrum, durable defence mechanism while exerting little selection pressure on pathogen populations. Relatively little is known about how disease tolerance is conferred, but most of the hypotheses suggest resource capture and resource-use traits such as large green canopy area, increased light extinction coefficient and a high source to sink balance. Disease tolerance in current wheat genotypes is generally associated with low yield potential, and for disease tolerance to be incorporated into commercial breeding it is important to determine whether this link can be disassociated.